Combating ageism through adult education and learning - Fragoso, António (2022)
The demographic data and projections show that the world is ageing at a high pace and that this has transversal consequences to society. The available data on ageism show that it constitutes the most prevalent form of discrimination in Europe. Whilst this seems logical because ageism, potentially, affects everybody (unlike sexism or racism), public debates on the phenomenon are rare. The awareness of people of its importance is minimal, the resources and investigation devoted to understanding it are relatively small and the initiatives towards combating ageism are not enough. There is a mismatch between the dimension of the phenomenon and the attention that we have given it. Ageism has various negative consequences for the older adults themselves; for the institutions at large (but especially for the working world institutions) and for countries. In a fast-ageing world that will witness structural changes in age groups, ageism is a complex phenomenon that needs to be counteracted. So far, in Europe, combating ageism through law and public policy seems to have produced poor results. However, the literature shows that adult education and learning can provide very effective means to improve the mutual knowledge between generations, combat myths and prejudice and deconstruct age-based stereotypes.